Determination of Heavy Metal Remediation to Soil from Community Buildings’ Rooftop - Yasin İlhanlı; Erman Ulker (Turkish Journal of Agriculture: Food Science and Technology)
Considering the importance of water in the world, the amount of usable water is not sufficient throughout the world, the existing available fresh water resources are not enough, therefore, water shortages may be encountered in the following years. Keeping the quality of water as it is demanded gains more importance than before. Particularly, heavy metals begin to interfere with groundwater resources, and the quantity of pollution growing due to industrialization, and urbanization. In the present study, the quantitative analysis of heavy metals in harvested rainwater from the rooftop of public buildings in Bornova, Izmir is investigated. The results show that a minimum of 5 μg of copper, 4 μg of zinc, 2.69 μg of lead, 0.095 μg of cadmium, 0.55 μg of chromium, 89,7 μg of iron, 0.96 μg of arsenic, 0.0119 μg of mercury and 3.88 μg of nickel should be tossed away for obtaining a liter of potable water. In conclusion, first flush diverters are recommended to convert these non-point pollutants to point source. Thus, municipalities can take necessary measures to protect the environment such as using phytoremediation and hyperaccumulator plants in sewages.